Simulation of passively Q-switched rate equation using saturable crystal Dy +2: CaF2 with ruby laser - Al-Kamel, A-M. K.; Hussain, Ali A-K.; Abed, K. H. (Iraqi Journal of Laser, 2009)
The simulation of passively Q-switching is four non – linear first order differential equations. The optimization of passively Q-switching simulation was carried out using the constrained Rosenbrock technique. The maximization option in this technique was utilized to the fourth equation as an objective function; the parameters, γa, γc and β as were dealt with as decision variables. A FORTRAN program was written to determine the optimum values of the decision variables through the simulation of the four coupled equations, for ruby laser Q–switched by Dy +2: CaF2.For different Dy +2:CaF2 molecules number, the values of decision variables was predicted using our written program. The relaxation time of Dy +2: CaF2, used with ruby was calculated using the predicted value of γa.